EXPLORING DIFFICULTIES EXPERIENCED BY STUDENTS WHEN SOLVING MATHEMATICAL PROBLEMSAND TEACHERS’ EFFORT TO HELP STUDENTS OVERCOME THESE DIFFICULTIES - Mutiawati Mutiawati (JOURNAL OF EDUCATION SCIENCE, 2015)
This study exploring teachers' difficulties students when solving problems and teachers’ effort to help students overcome these difficulties. Classroom practices and strategies teachers used in their attempts to foster student problem solving success were also studied. Data included analyses of interview transcriptions of students and teachers' responses. Findings from teachers' responses showed students' abilities to read and understand the problem was the most frequently cited difficulty; standardized testing and text difficulties were the most cited causes of those difficulties. Data analysis showed that students were not successful at obtaining solutions for the following reasons (1) Lack of comprehension of the problem posed, (2) Lack of strategy knowledge; (3) Inability to translate the problem into a mathematical form; (4) Inability to use the correct mathematics; (5) Inappropriate strategy used, (6) Incorrect formulation of the mathematical form; (7) Computational errors; (9) Imperfect mathematical knowledge; and (10) Misinterpretation of the problem. Keywords:solving mathematicalproblems, difficulties, students, teacher